PILGRIMAGE SITES AND THEIR CLASSIFICATION - Jasurbek Abdukadirov (Bright Mind Publishing, 2025)
This article provides information about the potential of pilgrimage tourism in Uzbekistan, the ongoing reforms in this field, and the historical background of pilgrimage sites located in the region. It also addresses issues related to their classification.
Keywords: Pilgrimage tourism, Uzbekistan, Bukhara, classification of pilgrimage objects, halal tourism, pilgrimage sites.